2017
DOI: 10.1128/aac.00223-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Care Exposure on Genotypic Antiseptic Tolerance in Staphylococcus aureus Infections in a Pediatric Population

Abstract: Staphylococcus aureus possessing either the smr gene or the qacA/B genes is associated with decreased susceptibility to chlorhexidine gluconate (CHG) and other antiseptics. Previous studies of antiseptic-tolerant staphylococci have focused largely on high-risk populations, and the exact role of health care exposure in the acquisition of these organisms is unclear. We sought to describe the risk factors and features of infection caused by antiseptic-tolerant S. aureus in a general pediatric population. Isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…In the present study, patients infected with qacA-and qacB-positive MRSA had common risk factors for health care-associated infections, including prior antibiotic use, central venous catheter in situ, ICU-acquired bacteremia, and nosocomial infection. These findings are consistent with previous studies revealing an association between the presence of qacA and qacB and health care exposure and provide evidence that the widespread use of CHG in hospital settings selects for genotypic chlorhexidine-tolerant strains that are able to survive in the presence of this antiseptic (14,19,23). In addition, as several previous studies have reported, we also found an association between chlorhexidine tolerance genes and resistance to non-␤-lactam antibiotics and a higher chlorhexidine MIC (11,14,23).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, patients infected with qacA-and qacB-positive MRSA had common risk factors for health care-associated infections, including prior antibiotic use, central venous catheter in situ, ICU-acquired bacteremia, and nosocomial infection. These findings are consistent with previous studies revealing an association between the presence of qacA and qacB and health care exposure and provide evidence that the widespread use of CHG in hospital settings selects for genotypic chlorhexidine-tolerant strains that are able to survive in the presence of this antiseptic (14,19,23). In addition, as several previous studies have reported, we also found an association between chlorhexidine tolerance genes and resistance to non-␤-lactam antibiotics and a higher chlorhexidine MIC (11,14,23).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies revealing an association between the presence of qacA and qacB and health care exposure and provide evidence that the widespread use of CHG in hospital settings selects for genotypic chlorhexidine-tolerant strains that are able to survive in the presence of this antiseptic (14,19,23). In addition, as several previous studies have reported, we also found an association between chlorhexidine tolerance genes and resistance to non-␤-lactam antibiotics and a higher chlorhexidine MIC (11,14,23). Although prior antibiotic use was independently associated with qacA-and qacB-positive MRSA in the present study, we could not determine whether there was antibiotic pressure on the selection of these microorganisms or whether this finding was simply a reflection of the coexistence of antimicrobial resistance genes on mobile genetic elements (24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20,[22][23][24] Pediatric-specific data are of relevance given the variable use of CHG in children's hospitals, particularly in neonatal intensive care units (NICUs), arising from concerns for systemic absorption and safety in young children. 25,26 We have reported that among a random sample of S. aureus isolates at Texas Children's Hospital (TCH), 32.8% possessed either smr or qacA/B, 21 suggesting our center represents a high prevalence region for AT.…”
mentioning
confidence: 97%
“…[17][18][19][20] In a recent study by our group, the presence of genotypic AT in S. aureus was independently associated with chronic medical comorbidities in the host and nosocomial acquisition of infection. 21 The relative prevalence of these genes among S. aureus in pediatric populations varies widely, ranging from 1% to 44.5% depending on geographic location and the type of patients studied. 20,[22][23][24] Pediatric-specific data are of relevance given the variable use of CHG in children's hospitals, particularly in neonatal intensive care units (NICUs), arising from concerns for systemic absorption and safety in young children.…”
mentioning
confidence: 99%